Porous-organic-framework-templated nitrogen-rich porous carbon as a more proficient electrocatalyst than Pt/C for the electrochemical reduction of oxygen - Pachfule, Pradip; Dhavale, Vishal M.; Kandambeth, Sharath; Kurungot, Sreekumar; Banerjee, Rahul (Chemistry-A European Journal, 2013)
Porous nitrogen-rich carbon (POF-C-1000) that was synthesized by using a porous organic framework (POF) as a self-sacrificing host template in a nanocasting process possessed a high degree of graphitization in an ordered structural arrangement with large domains and well-ordered arrays of carbon sheets. POF-C-1000 exhibits favorable electrocatalytic activity for the oxygen-reduction reaction (ORR) with a clear positive shift of about 40 mV in the onset potential compared to that of a traditional, commercially available Pt/C catalyst. In addition, irrespective of its moderate surface area (785 m2?g-1), POF-C-1000 showed a reasonable H2 adsorption of 1.6 wt?% (77 K) and a CO2 uptake of 3.5 mmol?g-1 (273 K).
Keywords: Adsorption; Electrochemistry; fuel cells; oxygen-reduction reaction; porous organic frameworks